How is the surface Atlantic water inflow through the Gibraltar Strait forecasted? A lagrangian validation of operational oceanographic services in the Alboran Sea and the Western Mediterranean. (November 2016) - Sotillo, M.G.; Amo-Baladrón, A.; Padorno, E.; Garcia-Ladona, E.; Orfila, A.; Rodríguez-Rubio, P.; Conti, D.; Madrid, J.A. Jiménez; de los Santos, F.J.; Fanjul, E. Alvarez
Abstract: An exhaustive validation of some of the operational ocean forecast products available in the Gibraltar Strait and the Alboran Sea is here presented. The skill of two ocean model solutions (derived from the Eulerian ocean forecast systems, such as the regional CMEMS IBI and the high resolution PdE SAMPA) in reproducing the complex surface dynamics in the above areas is evaluated. To this aim, in-situ measurements from the MEDESS-GIB drifter buoy database (comprising the Lagrangian positions, derived velocities and SST values) are used as the observational reference and the temporal coverage for the validation is 3 months (September to December 2014). Two metrics, a Lagrangian separation distance and a skill score, have been applied to evaluate the performance of the modelling systems in reproducing the observed trajectories. Furthermore, the SST validation with in-situ data is carried out by means of validating the model solutions with L3 satellite SST products. The Copernicus regional IBI products are evaluated in an extended domain, beyond the Alboran Sea, and covering western Mediterranean waters. This analysis reveals some strengths of the presented regional solution (i.e. realistic values of the Atlantic Jet in the Strait of Gibraltar area, realistic simulation of the Algerian Current). However, some shortcomings are also identified, with the major one being related to the simulated geographical position and intensity of the Alboran Gyres, particularly the western one. This performance limitation affects the IBI-modelled surface circulation in the entire Alboran Sea. On the other hand, the SAMPA system shows a more accurate model performance and it realistically reproduces the observed surface circulation in the area. The results reflect the effectiveness of the dynamical downscaling performed through the SAMPA system with respect to the regional IBI solution (in which SAMPA is nested), providing an objective measure of the potential added values introduced by the SAMPA downscaling solution in the Alboran Sea.